2013
DOI: 10.1111/fwb.12265
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of viral lysis and nanoflagellate grazing for prokaryote mortality in temperate lakes

Abstract: 1. We explored the factors that potentially affect viral abundance, viral life strategies (lytic versus lysogenic cycle) and the relative importance of viral lysis and heterotrophic nanoflagellate grazing for prokaryote mortality in the euphotic zone of 19 freshwater lakes in a single geographical region (the French Massif Central). 2. Flow cytometry indicated that viral abundance ranged from 0.5 to 26.3 9 10 7 viruses mL À1 , exceeding prokaryote abundance by c. 16-fold on average. Multiple regressions reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…A study by Parvathi et al (2013) on CE has attributed short-term variations in VP to various host processes and environmental factors, including light and salinity. The above findings are corroborated in this study with significant correlation ( p < 0.001) of VA with PA and BP, as previously reported for different environments (Parvathi et al, 2011; Winget et al, 2011; Payet and Suttle, 2013; Pradeep Ram and Sime-Ngando, 2014). The host parameters were influenced by seasonal salinity variations, which in turn triggered the spatial and seasonal variations in viral parameters.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Parvathi et al (2013) on CE has attributed short-term variations in VP to various host processes and environmental factors, including light and salinity. The above findings are corroborated in this study with significant correlation ( p < 0.001) of VA with PA and BP, as previously reported for different environments (Parvathi et al, 2011; Winget et al, 2011; Payet and Suttle, 2013; Pradeep Ram and Sime-Ngando, 2014). The host parameters were influenced by seasonal salinity variations, which in turn triggered the spatial and seasonal variations in viral parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, a significant part of this variability remained statistically unexplained in our study, corresponding to some abrupt shifts that were observed in close and chemically similar sampling sites. This could be partly due to biotic factors, such as predation or viral lysis pressures, which are well known for their influence on prokaryotic community abundance and structure (Ben Said et al, 2015;Louati et al, 2013;Ram et al, 2014;Sauret et al, 2015) but…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of doubling times as performed here (both using CARD-FISH or metagenomic abundances) was done according to the following assumptions: Firstly, estimates of average mortality by grazing (24%) and by viruses (31%) were obtained from prior observations from a relatively large sample of 19 lakes [ 68 ]. Taken together, a total of 55% mortality was assumed as a combined effect.…”
Section: Methodsmentioning
confidence: 99%